Beban Berat Demokrasi Partisipatoris (Studi Kasus Aceh Besar) - Teuku Kemal Fasya (Puslatbang KHAN, 2013)
This paper derives from qualitative research on the construction of local democracy in Aceh Besar, Aceh. The research describes the experience of special autonomy governance in one the districts in Aceh after the Helsinki peace accord prior to social-economy-cultural damage due to conflict and tsunami. It captures the role of social and political actors in terms of synergizing a balance and good representative and participatory democracy. The focus issue is on the elite and society level. In elite level, there is a lack of leadership skill that hinders the performance of local administrative, while on the society level there is yet an ability to participate and utilize the public sphere including responding toward public policies. The bad governance is reflected through the ongoing conflict surrounding 2012 local election. This experience of conflict during local election seems to relive the trauma of violent conflict and civil rights repression, resulted in political apathy and fatalism among the people. This is surely contradicts the spirit of new model on local democracy that is expected differently with the way it has been practiced in the central government.